Knowledge and Practice of Contraceptive Among Lactating Mothers Attending at Radda Maternal and Child Health and Family Planning Centre at Mirpur, Dhaka - Uddin, Mohammad Taslim; Barua, Shaibal (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background: As a natural child-spacing method breast feeding is very effective during the early post partum period. In Bangladesh it is believed that conception occurs very rarely during post partum and lactation period. Mothers nurse their children for long period, believing this is an easy, practical and natural method to delay or prevent a subsequent pregnancy. Since child-spacing effect of breast feeding gradually diminishes over time depending on personal and social circumstances breast feeding women during lactation need contraceptive methods which must be effective and safe and must not affect lactation. Methods: A descriptive type of cross sectional study was carried out, from July 2012 to December 2012, among 110 lactating mothers at RADDA Maternal and Child Health (MCH) and Family planning Centre, Mirpur, Dhaka with the objective of assessing their knowledge and practice on contraceptive methods. Results: Out of 110 respondents, 92 respondents having 1-2 children (83.64%) 79.35% were practicing contraception and 20.5% were not practicing any method and rest of 18 respondents having >2 children (16.36%), 77.78% were practicing contraception and 22.22% were not practicing contraception. Of the 91 respondents having children 1-2, 75.4% had average and above average knowledge and the rest 8.1% had below average knowledge on contraceptive methods. Of the 19 respondents having >2 children, 16.3% had average and above average knowledge and the rest (0.2%) had below average knowledge on contraceptive methods. The difference between the two groups in respect of practice and knowledge of contraception were found statistically insignificant. Conclusion: The study shows significant relation between the knowledge and practice of contraceptive with number of the children. There is significant difference between the knowledge among primary and secondary educated mothers and the practice of contraception varied with their education levels. All the respondents had knowledge about contraceptive methods but 20.9% were not practicing any methods due to various reasons. Chatt Maa Shi Hosp Med Coll J; Vol.17 (2); Jul 2018; Page 40-46